2021
DOI: 10.24018/ejbmr.2021.6.2.813
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Diversity Management on Organizational Performance: The Case of Ethio-Telecom South West Region

Abstract: The aim of this paper is examining the effect of diversity management on organizational performance by focusing on Ethio-Telecom (Ethiopian Telecommunication) South West region offices. Using Survey research design a quantitative data was randomly collected from a total of 120 employees. Path analysis was conducted to test the three research hypothesis. The result of empirical analysis showed that organizational diversity management constructs or dimensions (ethnicity, gender, and religion) are positively rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…No previous study has illustrated this relationship. However, the findings in (Hailu 2014;Al-Muhayfith and Shaiti 2020) partially support the current study findings. Both studies found that an IS (ERPS) influenced organizational performance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…No previous study has illustrated this relationship. However, the findings in (Hailu 2014;Al-Muhayfith and Shaiti 2020) partially support the current study findings. Both studies found that an IS (ERPS) influenced organizational performance.…”
Section: Discussionsupporting
confidence: 87%
“…An IS is basically a set of components used to collect, process, store, and analyze data and to provide relevant information to support management operations and decisions (Hailu 2014). An IS plays a significant role when it influences a firm's functions, performance, and productivity.…”
Section: The Moderating Role Of Is Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study will have a significant impact on the organization's performance and will help to effectively manage diversity practices in the workforce. Abdulhakim and Shimelis (2021) focused on the South West region offices of Ethiopian Telecommunication to investigate the impact of diversity management on organizational performance. A random sampling of quantitative data was taken from a total of 120 employees using the survey research design.…”
Section: Age Diversity On Organizational Performancementioning
confidence: 99%